Immediate Effect of Simple Bhramari Pranayama on Blood Pressure and Pulse Rate of Hypertensive and Normotensive Individuals: A Single-Arm Clinical Trial - Pratibha Hemant Rajbhoj; Satish D. Pathak; Ranjeet Singh Bhogal; Akshata Sudesh Badave; Santosh Pandey (Journal of Integrated Health Sciences)
Introduction: Hypertension, diabetes, and heart diseases are very common and silent noncommunicable diseases. If ignored, these will be life-threatening. As per recent yoga researches on hypertension, some of the yoga practices such as pranayama, meditation, and Kriya yoga have found to be very effective in managing hypertension and thereby controlling its adverse effects. Hence, the present study is undertaken to understand the effect of simple Bhramari pranayama on both hypertensive and normotensive individuals so as to help standardize this Pranayama and advise it as a preventive measure in the management of hypertension. Methods: The present study is a single-arm clinical trial. Ninety-seven participants, both male and females of age ranging from 30 to 60 years, were approached as the study participants. Of the 78 complying participants, 44 participants were hypertensive and 34 normotensives. A yoga expert taught Bhramari Pranayama one to one to all the participants. They were called on the following day for recording their blood pressure (BP) and pulse rate (PR) before and immediately after the thirty rounds of the practice. Results: Simple Bhramari Pranayama significantly lowered the systolic blood pressure (SBP) (P < 0.001), diastolic blood pressure (DBP) (P < 0.001*), and PR (P < 0.001*) of the hypertensive individuals (P < 0.001*). In the normotensives group also, a significant decrease in SBP (P < 0.001*), DBP (P < 0.05) and PR (P < 0.001*) was evident. However, the changes evident in normotensives were well within the normal range of BP and PR. Conclusion: The present study concludes that simple Bhramari Pranayama has significantly reduced the BP and PR in the hypertensive as well as in the normotensive participants immediately after its practice.